2014
DOI: 10.4028/www.scientific.net/amm.606.265
|View full text |Cite
|
Sign up to set email alerts
|

Application of Statistical Taguchi Method to Optimize Main Elements in the Residential Buildings in Malaysia Based Energy Consumption

Abstract: Today energy consumption is one of the controversial issues in the world. The rapid growing world energy consumption has already increased concern about the supply problems, heavy environmental effects such as global warming, climate change and etc. One of the most users of energy is residential buildings that consume the biggest share of energy. Growth in population, rising demand for buildings together causes to increase the upward trend in energy consumption. Therefore, energy efficiency in buildings plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It is one of the best optimization techniques to achieve high quality without consuming much time and cost [32]. The Taguchi method has recently been used in energy efficiency optimization in buildings studies [33].…”
Section: Design Of Experiments (Doe-taguchi Method) Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the best optimization techniques to achieve high quality without consuming much time and cost [32]. The Taguchi method has recently been used in energy efficiency optimization in buildings studies [33].…”
Section: Design Of Experiments (Doe-taguchi Method) Applicationmentioning
confidence: 99%
“…This method uses a fractional factorial order layout, termed Orthogonal Arrays (OA) to investigate the most effective energy retrofitting measures in order to reduce the number of simulations required [31]. The Taguchi method uses the signal-to-noise ratio (SNR), which is a measure of robustness that aims to reduce the effect of noise and optimize the performance of the process [33].…”
Section: Design Of Experiments (Doe-taguchi Method) Applicationmentioning
confidence: 99%
“…For the analysis of the existing BSC transportation system, the literature consists of some mathematical, static, and simulation methods [14]. One of the best ones is simulation modeling since it is highly flexible and can simulate and evaluate both static and dynamic systems considering variability and uncertainty between systems -like manufacturing lines [44], ports and maritime industry [45], healthcare systems [46], supply chains [47], construction sector [48], and buildings [49]. This method has been recognized as a key technique in BSC research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Final result indicated that changing ceilings and ceiling materials play a significant role to decrease energy consumption [3]. Additionally, in another study, statistical Taguchi method was proposed to find the optimum value of the main parameters of buildings that are window, ceiling, and wall along with the effect of uncontrollable factors such as humidity, temperature, and air flow in residential buildings [9]. In another research, building simulation and DOE were combined to evaluate the effect of main climate factors on energy saving and cooling load.…”
Section: Literature Reviewmentioning
confidence: 99%